A biblical mnemohistory of 'Egypt' : Exodus as the legitimation of Israelite continuity - Geobey, Ronald A. (Trinity College (Dublin, Ireland). Department of Near and Middle Eastern Studies, 2015)
The aim of this thesis was to chart the evolution of the tradition in the Hebrew Bible of a migration from Egypt as it relates to the development of Israelite identity, with a view to negotiating a position between the poles of 'maximalist' or 'conservative' scholars maintaining the relative historicity of the received form (that which we know as Exodus); and 'minimalist' or 'revisionist' scholars pushing the date for the composition of Exodus into increasingly later periods in the development of Judaism. I have argued for a 'mnemohistorical' approach to critical analyses of the historicity of the migration tradition, seeing Exodus as the final product in a long history of the development of a tradition integral to the preservation of Israelite identity. While this in itself is not a new concept, I have identified significant 'memory contexts' in which revitalised incarnations of the migration tradition appear to be associated with distorted memories of identity (re-)negotiation.
Embargo End Date: 2022-01-01
Keywords: Near & Middle Eastern Studies, Ph.D.; Ph.D. Trinity College Dublin, 2015